Outcome of Low-Intensity Pulsed Ultrasound (LIPUS) for Opening Wedge High Tibial Osteotomy. Issue 7 (July 2017) - Saito, Ryusuke; Nagase, Tsuyoshi; Tateishi, Tomohiko; Shimizu, Sadanori; Kato, Takuya; Nakagawa, Teruhiko; Tsutiya, Masamitsu
Abstract : Objective: Opening Wedge High Tibial Osteotomy (OWHTO) for knee osteoarthritis and for osteonecrosis has reported good results. Use of low intensity pulsed ultrasound (LIPUS) after OWHTO had become an option for the treatment of OWHTO since April 2016. The purpose of this study was to examine whether LIPUS has an accelerating effect on synostosis after OWHTO. Materials and Methods: The control subjects were 24 patients with a total of 26 knees (9 male with knees and 15 female with 17 knees treated) treated with OWHTO only. OWHTO was performed from April 2015 to March 2016 (non-LIPUS control group). The average age of the patients was 61 years. The test subjects were 25 patients with a total of 27 knees (8 male with 9 knees and 17 female with 18 knees treated) treated with OWHTO and LIPUS. OWHTO was performed from April 2016 until the present. LIPUS was started after the surgery (LIPUS + group). The average age was 64.6 years. FTA, ROM, intraoperative open angle, and the time to bone union were examined. Results: There was no difference between the 2 groups in FTA, ROM, and open angle. Synostosis was obtained in 18 knees in the control group (no LIPUS) with an average duration of 8.4 months. The LIPUS + group had a short observation period with none of the patients experiencing bone union. Discussion: The synostosis promoting effect of LIPUS is expected. In this study, there were no bone union cases because of the short observation period. It is necessary to extend the follow-up period, and clarify the utility of LIPUS.